An All‐Optical, Actively Q‐Switched Fiber Laser by an Antimonene‐Based Optical Modulator. Issue 4 (24th January 2019) - Wang, Yunzheng; Huang, Weichun; Wang, Cong; Guo, Jia; Zhang, Feng; Song, Yufeng; Ge, Yanqi; Wu, Leiming; Liu, Jie; Li, Jianqing; Zhang, Han
Abstract: Q‐switched fiber lasers are of great interest in industrial material processing, nonlinear frequency conversion, spectroscopy etc. However, passive Q‐switching possesses drawbacks of degradation and failure of the saturable absorber and the difficulty in accurate modification of the repetition rate. To overcome these issues, active Q‐switching that can normally modulate the cavity quality‐factor by an externally‐driven Q‐switcher is in high demand. Herein, an actively Q‐switched laser with antimonene‐based all‐optical modulator is devised based on the high photo‐thermal efficiency (48%) and broadband response in antimonene. It is demonstrated that this actively modulated laser represents all‐optically tunable output parameters (e.g., output repetition rate), environmental stability, and easy synchronization. It is anticipated that this actively antimonene‐based all‐optical modulator with advantages of large modulation depth, low energy consumption, and high conversion efficiency has great potential in all‐optical information processing and pulsed laser engineering. Abstract : An all‐optical, actively Q‐switched fiber laser enabled by an antimonene‐based all‐optical modulator is demonstrated by taking advantage of the high photo‐thermal efficiency and broadband response in antimonene. It is demonstrated that this actively modulated fiber laser represents all‐optically tunable output parameters, environmental stability, and easy synchronization, and has great potentials in information processing and pulsed laser.